TP53 gene mutations of lung cancer patients in upper northern Thailand and environmental risk factors - Kanokkan Bumroongkit (2018)
TP53 mutations are observed in about 40-70% of lung cancer tissues, and the hot spot codon mutations are in exons 5 through 8. Previous studies revealed that the distinct TP53 mutational pattern between population groups may be due to different racial or exogenous factors. This research aims to identify risk factors that influence TP53 gene mutation in lung cancer patients residing areas with high lung cancer incidence, in the upper northern part of Thailand. Germline TP53 mutational analyses were also performed to determine the inherited cancer predisposition. Exons 5-8 of the TP53 gene were analyzed by sequencing DNA of cancerous tissue and peripheral blood leukocyte samples from 55 non-small lung cell cancer patients. The results showed that the TP53 germline mutation was not found in all patients, indicating that the TP53 germline mutations were not exclusively responsible for cancer predisposition in this group of lung cancer patients. A total of 19 somatic mutations were found in 18 patients. Mutations were predominantly found in exons, with only 10.53% observed at the splice sites of intron 7. No characteristic hot spot codons were observed. The data suggest that TP53 mutations in this study group are induced by exposure to substances other than tobacco smoke. Pesticide exposure or habitation in poorly ventilated houses may instead be related to the tumorigenesis of lung cancer via TP53 mutations. © 2008 Elsevier Inc. All rights reserved.